2022
DOI: 10.5812/iranjradiol-117992
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-centric Evaluation of Deep Learning Models for Segmentation of COVID-19 Lung Lesions on Chest CT Scans

Abstract: Background: Chest computed tomography (CT) scan is one of the most common tools used for the diagnosis of patients with coronavirus disease 2019 (COVID-19). While segmentation of COVID-19 lung lesions by radiologists can be time-consuming, the application of advanced deep learning techniques for automated segmentation can be a promising step toward the management of this infection and similar diseases in the future. Objectives: This study aimed to evaluate the performance and generalizability of deep learning-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…A deep learning approach based on the U-Net framework (12) was implemented to segment the COVID-19 infection regions on the CT slices. Previous studies have shown that VGG16-based UNet model was successful in COVID-19 lesion segmentation [11,[15][16][17]. This model can localize abnormal areas in the image and distinguish their boundaries [18].…”
Section: Plos Onementioning
confidence: 94%
See 1 more Smart Citation
“…A deep learning approach based on the U-Net framework (12) was implemented to segment the COVID-19 infection regions on the CT slices. Previous studies have shown that VGG16-based UNet model was successful in COVID-19 lesion segmentation [11,[15][16][17]. This model can localize abnormal areas in the image and distinguish their boundaries [18].…”
Section: Plos Onementioning
confidence: 94%
“…In order to train the model, we used a dataset that was introduced in a previous study. This dataset was approved under the ethical approval code IR.TUMS.VCR.REC.1399.488, titled "Clinical Feasibility Study of National Teleradiology System for COVID-19" [11]. It consists of 297 subjects (men, n = 167 [56.6%]; age 54.3±19.2 years) with 148 in critical condition.…”
Section: Study Design and Populationmentioning
confidence: 99%